Macrophages From Subjects With Isolated GH/IGF-I Deficiency Due to a GHRH Receptor Gene Mutation Are Less Prone to Infection by Leishmania amazonensis - Barrios, Mônica R.; Campos, Viviane C.; Peres, Nalu T. A.; de Oliveira, Laís L.; Cazzaniga, Rodrigo A.; Santos, Márcio B.; Aires, Murilo B.; Silva, Ricardo L. L.; Barreto, Aline; Goto, Hiro; Almeida, Roque P.; Salvatori, Roberto; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Isolated growth hormone (GH) deficiency (IGHD) affects approximately 1 in 4,000 to 1 in 10,000 individuals worldwide. We have previously described a large cohort of subjects with IGHD due to a homozygous mutation in the GH releasing hormone (GHRH) receptor gene. These subjects exhibit throughout the life very low levels of GH and its principal mediator, the Insulin Growth Factor-I (IGF-I). The facilitating role of IGF-I in the infection of mice macrophages by different Leishmania strains is well known. Nevertheless, the role of IGF-I in Leishmania infection of human macrophages has not been studied. This study aimed to evaluate the behavior of Leishmania infection in vitro in macrophages from untreated IGHD subjects. To this end, blood samples were collected from 14 IGHD individuals and 14 age and sex-matched healthy controls. Monocytes were isolated and derived into macrophages and infected with a strain of Leishmania amazonensis. In addition, IGF-I was added to culture medium to evaluate its effect on the infection. Cytokines were measured in the culture supernatants. We found that macrophages from IGHD subjects were more resistant to Leishmania infection compared to GH sufficient controls. Both inflammatory and anti-inflammatory cytokines increase only in the supernatants of the control macrophages. Addition of IGF-I to the culture medium increased infection rates. In conclusion, we demonstrated that IGF-I is crucial for Leishmania infection of human macrophages.